Referencia
Práctica
Premium
Acceder
Español
English
Español ✔
日本語
简体中文
繁體中文
6
x
−
3
=
2
6x-3=2
6
x
−
3
=
2
+
−
.
ln
>
<
×
÷
/
log
≥
≤
(
)
log
x
=
%
Elige El Tema
Ejemplos
"(x+1)/2+4=7"
"factor x^2+5x+6"
"integrate cos(x)^3"
Más »
6x-3=2
6x-3=2
6x-3=2
1
Suma
3
3
3
a ambos lados.
6
x
=
2
+
3
6x=2+3
6
x
=
2
+
3
2
Simplifica
2
+
3
2+3
2
+
3
a
5
5
5
.
6
x
=
5
6x=5
6
x
=
5
3
Divide ambos lados por
6
6
6
.
x
=
5
6
x=\frac{5}{6}
x
=
6
5
Hecho
Forma Decimal: 0.833333
Comprobar Respuesta ▼
x=5/6
¿Te gusta esta solución? ¡Compártelo!
Copy Link
¿Cómo podemos hacer esta solución más útil?